Names, Varieties and Ideologies in Revived Cornish - Davies-Deacon, Merryn (Studia Celtica Posnaniensia, 2017)
The attribution of names is a significant process that often highlights concerns over identity, ideology and ownership. Within the fields of minority languages and Celtic Studies, such concerns are especially pertinent given that the identities in question are frequently perceived as under threat from dominant cultures. The effect of concerns caused by this can be examined with reference to revived Cornish, which became divided into three major varieties in the later twentieth century; by examining the names of these varieties, we can draw conclusions about how they are perceived, or we are invited to perceive them. The motivations of those involved in the Cornish language revival are equally reflected in the names of the organisations and bodies they have formed, which equally contribute to the legitimation of revived Cornish. This paper examines both these categories of name, as well as the phenomenon of Kernowisation, a term coined by Harasta (2013) to refer to the adoption of Cornish personal names, and here extended to the use of Cornish names in otherwise English-language contexts. Examining the names that have been implemented during the Cornish language revival, and the ways in which they are used or indeed refused by those involved, gives us an insight into the various ideologies that steer the revival process. Within the context of the precarious nature of Cornish and Celtic identity, we can identify the concerns of those involved in the Cornish revival movement and highlight the role of naming as an activity of legitimation, showing how the diversity of names that occur reflects an equally diverse range of motivations and influences.